Verbraucherresilienz: Risikofaktoren, Vulnerabilitäten und Interventionen - Achtziger, Anja; Kenning, Peter (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The topic of resilience has received attention in the behavioural sciences since the 1950s. In particular, the Kauai Longitudinal Study by Emmy Werner was groundbreaking in terms of resilience research. In recent years, this research has also attracted the interest of the consumer sciences. Although fundamentally scarce, corresponding research either deals with the resilience of consumers in the context of extreme events such as floods (Marg 2016) and terrorist attacks (Rew & Minor 2018) or with recurring stress factors, which can be located, for example, in the context of analogue or digital consumption. Against this backdrop, this book aims to highlight the state of research in the field of ‘consumer resilience’ and provide impetus for further research.With contributions byAnja Achtziger | Carmela Aprea | Tabea Bucher-Koenen | Marius Cziriak | Maja Eilender | Martin Endreß | Arnd Florack | Donya Gilan | Anja Göritz | Stefanie Graefe | Peter Kenning | Jörn Lamla | Kathrin Loer | Max Lohner | René Riedl | Christiane Rohleder | Sarah K. Schäfer | Hanna Schramm-Klein